Representing Italy through food - Naccarato, Peter, 1970-; Nowak, Zachary; Eckert, Elgin K. (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"Italy has long been romanticized as an idyllic place. Italian food and foodways play an important part in this romanticization - from bountiful bowls of fresh pasta to bottles of Tuscan wine. While such images oversimplify the complex reality of modern Italy, they are central to how Italy is imagined by Italians and non-Italians alike. Representing Italy through Food is the first book to examine how these perceptions are constructed, sustained, promoted, and challenged. Recognizing the power of representations to construct reality, the book explores how Italian food and foodways are represented across the media - from literature to film and television, from cookbooks to social media, and from marketing campaigns to advertisements. Bringing together established scholars such as Massimo Montanari and Ken Albala with emerging scholars in the field, the thirteen chapters offer new perspectives on Italian food and culture. Featuring both local and global perspectives - which examine Italian food in the United States, Australia and Israel - the book reveals the power of representations across historical, geographic, socio-economic, and cultural boundaries and asks if there is anything that makes Italy unique. An important contribution to our understanding of the enduring power of Italy, Italian culture and Italian food - both in Italy and beyond. Essential reading for students and scholars in food studies, Italian studies, media studies, and cultural studies"--